2016
DOI: 10.25011/cim.v39i6.27527
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with work-related musculoskeletal disorders in dentistry

Abstract: Purpose: To evaluate musculoskeletal system-related complaints; identify regions at risk in dentists by observing and inquiring the dentists at work; and find out the associations with age, sex, working years, academic position and departments, positions during work and daily working hours. Methods: Modified Nordic Questionnaire (m-nMQ) was used to evaluate pain, hospital admissions and absenteeism. Quick Exposure Check (QEC) form was utilized to assess risk exposure levels related with low-back, neck, hand-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 14 publications
1
22
0
2
Order By: Relevance
“…Maintaining a certain posture for a long time while working is dependent on permanent muscle loading. [5][6][7][8][9] Muscle loading that occurs to maintain this working position causes fatigue and decreases muscle strength. This posture is directly related to the person's mechanical competence and physiological functions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Maintaining a certain posture for a long time while working is dependent on permanent muscle loading. [5][6][7][8][9] Muscle loading that occurs to maintain this working position causes fatigue and decreases muscle strength. This posture is directly related to the person's mechanical competence and physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations show that the causes of early degenerative changes in the lumbar region include compression, bending, and shear stress due to wrong body postures. [8][9][10] In septorhinoplasty, these effects occur in the lumbar region and lead to the development of low back pain. In this study, the detection of lumbar pathologies at such a level that they were seen as lumbar degeneration on MRI findings in 14 doctors performing rhinoplasty suggests that these factors may have serious consequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that psychosocial stress significantly influenced the appearance of MSD. Finally, Bozkurt et al [104] evaluated dental professionals, identifying regions of risk and their relation to the different qualitative variables of the individual. The symptoms of MSD were more frequent in women and research assistants.…”
Section: Activities Of Attending Human Health and Social Assistancementioning
confidence: 99%